An economic analysis of flood and center pivot irrigation system modifications - DeLano, Daniel R., author; Williams, Jeffery R., author; O'Brien, Daniel M., author (Colorado State University. Libraries, 1997)
An after-tax net present value(NPV) analysis of investing in three irrigation system modifications for the production of corn, grain sorghum, wheat, and alfalfa is conducted. Modifying a high pressure center pivot with low-drift nozzles and adding surge valves to a gated pipe system is economically feasible for each crop.
Not digitized by CSUL Digital Services.
Presented at the Central Plains irrigation short course and exposition on February 4, 1997 at the Colby Community Building in Colby, Kansas.